University students’ health literacy during the COVID-19 pandemic: a review of observational studies - Cristina Ciupitu-Plath; Brian C. Carrell; Ekaterini Papadopoulou (Cogent Education)
University students faced significant personal and educational challenges during the COVID-19 pandemic. With health literacy (HL) being an important resource in navigating the pandemic-associated overabundance of information, this study aimed to summarize the current literature on university students’ HL during the pandemic. We searched PubMed, CINAHL Complete, APA PsychINFO, and ERIC for relevant publications. We included studies that focused on college or university students, used standardized HL assessments in community samples, and reported HL data collected between March 2020 and May 2023. Data extraction focused primarily on students’ HL levels and correlates. Although students displayed moderate to high HL, creating written content and evaluating the reliability of online information posed the greatest challenges. HL varied with preferred information sources. Younger age, female gender, low socioeconomic status, and enrollment in an undergraduate or non-health science program were typically associated with lower HL. HL significantly contributed to better health outcomes through improved health behaviors. Based on our findings, university students could benefit from early HL training and support assessing the reliability of information sources and communicating clearly in writing. More research is needed on the HL of students from traditionally marginalized populations and its impact on health outcomes during public health crises.